(untitled) (Journal of Oriental Studies, 2016)
This article covers the period of Turkish language, including the reform of Atatürk. Ataturk, seeking to bring Turkey to the level of modern civilization, has implemented a number of reforms in the country. All languages other than Turkish, were banned. The whole system of education based on the upbringing of the Turkish spirit of national unity. These postulates have been proclaimed in the Constitution in 1924.